Obesity and Eating Disorders: Evidences for Differentiation - Rizzo, Amelia; Costantino, Elisabetta; Peronace, Domy; Alfa, Rossella; Di Pauli, Daniele (KMAN Counseling & Psychology Nexus, 2024)
Excess weight is often incorrectly linked to pathological eating behaviors without considering the complexity of underlying causes. The aim of this study is to explore the intersections between obesity and Eating Disorders, with particular reference to the Binge Eating Disorder (BED). This study analyzed (1) the presence of BED in a population of 293 individuals affected by obesity using the Binge Eating Questionnaire and (2) the correlations between body weight (BMI) and eating behavior (Eating Disorder Questionnaire). Data analysis revealed that only 12% of the sample met the criteria for an Eating Disorder and that the body mass index was not correlated with pathological eating behavior but with body dissatisfaction (p<.001). The study suggests that only a modest percentage of individuals with obesity have comorbid Eating Disorders, and that weight is correlated with a state of distress (internalized stigma?) that may constitute a maintenance factor hindering health behaviors. This study highlights the need for differentiated and personalized clinical and therapeutic interventions.